Wpływ odłogowania i dodatku trocin iglastych do gleby porolnej na jej właściwości chemiczne i zbiorowisko grzybów ektomykoryzowych 15-letniej sosny zwyczajnej - Małecka, Monika; Hilszczańska, Dorota (Leśne Prace Badawcze, 2015)
Changes in chemical compounds and in ectomycorrhizal structure were determined for Scots pine growing on post agricultural soil lying fallow for 3, 6 and 15 years, after amendment with pine sawdust. Soil without any amendments was used as the control treatment. Comparing the ectomycorrhizal structure 15 years after the application of pine sawdust revealed no significant differences in abundance or species richness between soil with and without organic enrichment. The results showed that the ectomycorrhizal status depends on soil conditions (soil pH, nitrogen content), which remain unaffected by saw dust application.In all treatments, the most frequently occurring ectomycorrhizae genera were Dermocybe , Hebeloma , Suillus , Tomentella and Tricholoma . Two species ( Paxillus involutus, Amanita muscaria ) were specific to the control plots that lay fallow for 15 years.